Nilai Pendidikan Karakter Dalam Lirik Lagu Gali Lobang Tutup Lobang Karya Rhoma Irama: Sebuah Analisis Konten - Yogi Fery Hidayat (Edukasiana: Journal of Islamic Education, 2023)
Character education is an education that aims to develop the character or morals of a person so that they can act as good and quality citizens. Character education is very important to be built in the world of education because it can help shape good personalities in the younger generation. This study aims to analyze the values of character education in the lyrics of Gali Lobang Tutup Lobang by Rhoma Irama. The author utilized a content analysis approach and analyzed the lyrics qualitatively. The results of the study indicate that the song conveys important messages regarding character education values such as simplicity, independence, responsibility, and healthy living. The song also contains significant social, cultural, and historical contexts in the life of the Indonesian nation. These messages are highly relevant in daily life and can help individuals become more responsible and forward-thinking. Keywords: character education, Rhoma Irama, Gali Lobang Tutup Lobang, content analysis.